Analysis of the History of Islam: From Its Origins to Its Spread Across the Archipelago - Yuveka Talitha Ardi Ningrum (Institut Agama Islam Al-Fatimah Bojonegoro, 2025)
The history of Islam has been a long journey, especially for the people of Indonesia. Islam originated in the Arabian Peninsula and was spread worldwide through the efforts of the prophets, including Prophet Muhammad SAW and the caliphs. However, various theories and perspectives continue to debate the process of Islam's arrival in the Nusantara. This study aims to provide a deeper understanding of the history of Islam, both globally and in the Nusantara, now known as Indonesia. The research employs qualitative and historical methods, where the qualitative method focuses on understanding social and cultural phenomena descriptively, while the historical method analyzes past data to enrich historical knowledge. Data was collected through documentation, analysis, and the compilation of references, utilizing various sources such as documents, books, and journals. The results of this study are expected to offer insights into the origins of Islam and its spread across the world, including to the Nusantara